2005
DOI: 10.1074/jbc.m411626200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Platelet-derived Growth Factor-induced Cell Growth Signaling by a Short Interfering RNA for EWS-Fli1 via Down-regulation of Phospholipase D2 in Ewing Sarcoma Cells

Abstract: EWS-Ewing sarcoma and other peripheral primitive neuroectodermal tumors are pediatric malignant solid tumors, Ͼ95% of which show the chromosomal translocations t(11;22, q24;q12) or t(21;22, q22;q12), which produce the fusion genes EWS-Fli1 and EWS-erg, respectively (1-4). Cytogenetic and molecular analyses of these translocation products have revealed that the 5Ј-region of the EWS gene (from band 22q12) is fused to the 3Ј-region of either the Fli-1 gene (from band 11q24) or the erg gene (from band 21q22), both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 42 publications
(52 reference statements)
4
42
0
Order By: Relevance
“…Endogenous levels of PA are low in resting cells, and PLD activity is tightly regulated by mechanisms that control secretion, migration, survival and proliferation of cells. 1,2 PLD is activated by a variety of mitogens, including epidermal growth factor (EGF), platelet-derived growth factor (PDGF) and interleukin 1b (IL-1b), [3][4][5][6][7] and its involvement in many cellular biological processes, including cell proliferation, survival, vesicular trafficking and secretion, has been demonstrated. 1,8 Two distinct isoforms of mammalian PLD, PLD1 and PLD2, have been identified.…”
mentioning
confidence: 99%
“…Endogenous levels of PA are low in resting cells, and PLD activity is tightly regulated by mechanisms that control secretion, migration, survival and proliferation of cells. 1,2 PLD is activated by a variety of mitogens, including epidermal growth factor (EGF), platelet-derived growth factor (PDGF) and interleukin 1b (IL-1b), [3][4][5][6][7] and its involvement in many cellular biological processes, including cell proliferation, survival, vesicular trafficking and secretion, has been demonstrated. 1,8 Two distinct isoforms of mammalian PLD, PLD1 and PLD2, have been identified.…”
mentioning
confidence: 99%
“…A recent study showed that the reduced EWS/Fli-1 expression by using siRNA induces downregulation of PLD2 protein expression (Nozawa et al, 2005). However, the mechanism of PLD2 gene expression by EWS/ Fli-1 was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…siRNA of PLD2 and of EWS were obtained from Sigma Genosys (Hokkaido, Japan). The sequence of siRNAs of EWS and of PLD2 was according to Nozawa et al (2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLD plays a role in growth factor-induced cellular proliferation [3][4][5][6] and facilitates oncogenic transformation [7][8][9][10]. Endogenous PLD activity is significantly increased in several types of cancers [11][12][13][14][15], as well as in cell lines transformed with oncogenes [4,5,8,10,[16][17][18][19]. PLD may participate in the activation of p42/44 ERK via Raf-1 translocation to the plasma membrane [20][21][22][23], as well as in the survival signaling mediated by PI3K/AKT activation [24].…”
Section: Introductionmentioning
confidence: 99%